Ketidaktepatan Penggunaan Inga No Setsuzokugo dan Keiki No Setsuzokugo dalam Sakubun Mahasiswa Bahasa Jepang Angkatan 2016 - Wulandari, Siti (Universitas Muhammadiyah Yogyakarta, 2020)
The purpose of this study is to classify the inaccuracies of inga no setsuzokugo types (conjunctions of cause and effect) and keiki no setsuzokugo (adverbial conjunction) that often occur because some of the setsuzokugo have the same meaning in Indonesian. These inaccuracies made the writer's intended message could not be understood. The data in this study were sentences in Japanese essays in which there are inaccurate uses of setsuzokugo by class 2016 from the Japanese Language Department, State University of Surabaya. Subjects used in the study were a total of 20 people and were decided based on random classes. The method used was descriptive, while the data analysis technique used techniques for segmenting immediate constituents technique or abbreviated as BUL.Â Also, there were 3 other supporting techniques, such as advanced and deletion techniques, adding interruption and substitution techniques.Â The results of this study indicated that the type of inga no setsuzokugo in which inaccuracies often occurred was